Comparison of Radiography and Ultrasonography for Diagnosis of Diaphragmatic Hernia in Bovines - Hakim Athar; Jitender Mohindroo; Kiranjeet Singh; Ashwani Kumar; Mulinti Raghunath (Veterinary Medicine International)
The present study was conducted on 101 animals suffering from thoracoabdominal disorders; out of which twenty seven animals (twenty six buffaloes and one cow) were diagnosed with diaphragmatic hernia based on clinical signs, radiography, ultrasonography, and left flank laparorumenotomy. Radiography alone confirmed diaphragmatic hernia in 18 cases (66.67%) with a sac-like structure cranial to the diaphragm. In 15 animals the sac contained metallic densities while in three cases a sac-like structure with no metallic densities was present. Ultrasonography was helpful in confirming diaphragmatic hernia in 23 cases (85.18%) and ultrasonographically reticular motility was evident at the level of 4th/5th intercostal space in all the animals. B+M mode ultrasonography was used for the first time for diagnosis of diaphragmatic hernia in bovines and the results suggested that ultrasonography was a reliable diagnostic modality for diaphragmatic hernia in bovines.